COMPANIONSHIP ON EDUCATION AND INTRODUCTION TO BAT SPECIES IN BRAJA HARJOSARI AND LABUHAN RATU VII, EAST LAMPUNG - Elly Lestari Rustiati; Dian Neli Pratiwi; Enny Saswiyanti; Vidya Kurniasih; Sevira Nur Azmi; Elfita Nova Yunior; Raden Fadly Bayu Dwiyoga; Priyambodo; Eko Agus Prihanto; Ahyul Heni; Dwi Ayu Febriyani; Waryoko Susandi; I Wayan Tony Candra; Sunandar (Jurnal Abdisci, 2024)
Under the HETI Project Program of Universitas Lampung 2023/2024, education and introduction to bats have been conducted in Braja Harjosari and Labuhan Ratu VII, East Lampung. Knowledge about bats and their ecological roles is essential as a conservation effort, particularly in residential areas adjacent to natural bat habitats. Information on bats, including their natural habitats, behaviors, and roles in supporting human life, as well as general species identification, was provided. The selection of locations, mist net installation, capture, handling, and release were demonstrated, including oral swab sample collection. The community’s response and enthusiasm were very positive in understanding bats as wildlife and their roles in human life.